1996
DOI: 10.1111/j.1747-4469.1996.tb00090.x
|View full text |Cite
|
Sign up to set email alerts
|

Corporations in Court: Big Business Litigation in U. S. Federal Courts, 1971–1991

Abstract: This article provides an overview of federal litigation involving the largest 2,000 U. S. corporations over the period 1971–91. Reporting from a unique data set of the authors’construction, it finds that althugh the aggregate volume of business litigation grew during the 1970s and early 1980s, it has actually been declining in recent years in all major categories of cases; business‐related litigation is heavily concentrated, with an extremely limited number of business “mega‐litigants” accounting for most of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 12 publications
0
25
0
1
Order By: Relevance
“…Galanter's hypothesis as to the advantages of``repeat players'' in litigation has been corroborated by many studies in the U.S. (Wheeler et al 1987;Sheehan et al 1992;Dunworth & Rogers 1996) as well as in other countries such as England (Atkins 1991) and Canada (McCormick 1993). While these studies found that government agencies as well as other repeat players enjoyed high success rates in litigation, they did not address the issue of the mechanisms by which repeat players achieved higher success rates than other litigants.…”
Section: Why Groups Are Successful Litigantsmentioning
confidence: 99%
“…Galanter's hypothesis as to the advantages of``repeat players'' in litigation has been corroborated by many studies in the U.S. (Wheeler et al 1987;Sheehan et al 1992;Dunworth & Rogers 1996) as well as in other countries such as England (Atkins 1991) and Canada (McCormick 1993). While these studies found that government agencies as well as other repeat players enjoyed high success rates in litigation, they did not address the issue of the mechanisms by which repeat players achieved higher success rates than other litigants.…”
Section: Why Groups Are Successful Litigantsmentioning
confidence: 99%
“…Accordingly, their decisions reflect the existing disparities in wealth and power in society, while the courts themselves are neutral (if not indifferent) to the inequalities entailed by their institutional passivity and ideological detachment (Galanter 1974:119-20).1 The theory has been corroborated by studies of the appellate courts in the United States Songer et al 1999) as well as of district courts (Dunworth & Rogers 1996) and, to a lesser degree, in states' supreme courts (Wheeler et al 1987;Farole 1999). Accordingly, their decisions reflect the existing disparities in wealth and power in society, while the courts themselves are neutral (if not indifferent) to the inequalities entailed by their institutional passivity and ideological detachment (Galanter 1974:119-20).1 The theory has been corroborated by studies of the appellate courts in the United States Songer et al 1999) as well as of district courts (Dunworth & Rogers 1996) and, to a lesser degree, in states' supreme courts (Wheeler et al 1987;Farole 1999).…”
mentioning
confidence: 99%
“…For example, issues of confl ict resolution in markets can be framed in terms of formal external control over organizational life (Hawkins 1984 ;Reiss 1984 ;Shapiro 1984 ;Vaughan 1983 ), but also in terms of more informal mechanisms such as reputation and ostracising (Macaulay 1963 ) or private arbitration (Dezalay and Garth 1996 ;Lemercier 2007 ). Both formal and informal processes help interdependent managers to monitor and sanction each other before resorting to well-defi ned but costly court procedures (Cheit and Gersen 2000 ;Dunworth and Rogers 1996 ;Macaulay 1963 ;Rooks et al 2000 ;Lazega 1994Lazega , 2001.…”
Section: Multilevel Logic Social Control and Morphogenesismentioning
confidence: 99%